Paediatric cystolitholapaxy through the Mitrofanoff/Monti channel. Issue 5 (October 2018) - Thomas, J.S.; Smeulders, N.; Yankovic, F.; Undre, S.; Mushtaq, I.; López, P.-J.; Cuckow, P.
Summary: Introduction: Bladder calculi are a known complication of bladder augmentation. Open cystolithotomy remains the preferred option for treating large or multiple stones. Increasingly, however, minimal access techniques have been used. Reports of Mitrofanoff cystolitholapaxy are rare and have been limited to adults. This study presented a two centre series of children treated by cystolitholapaxy via the Mitrofanoff/Monti channel. Materials and methods: With institutional approval the current study retrospectively reviewed and identified 14 patients, on a prospective database, who underwent Mitrofanoff cystolitholapaxy to treat bladder calculi at two independent institutions in the UK and Chile between 2004 and 2016. It looked at patient demographics, surgical technique, stone clearance and recurrence, as well as leak or catheterisation difficulties of the Mitrofanoff/Monti channel post-procedure. Results: Fourteen patients underwent Mitrofanoff cystolitholapaxy during the period 2004–2016. One patient was excluded due to lack of follow-up. The remaining 13 patients were aged 5–22 (median 14) years at the time of the procedure. Their underlying diagnoses were four neuropathic bladders, four bladder exstrophy, four cloacal exstrophy and one posterior urethral valve. Patients underwent augmentation cystoplasty at a median age of 5 (range 1–15) years, using ileum in 10 and sigmoid colon in three. The channel for clean intermittent catheterisation was an appendix Mitrofanoff in nine and a Monti channel in four. An Amplatz sheath was placed through the Mitrofanoff to allow safe access to the bladder for treating the stones (see Summary Table). Recurrent stones were treated using the same technique. Stone and channel outcomes were analysed for each procedure. There were 22 procedures in 13 patients; five (38%) patients had recurrent stones. Median time to recurrence was 6 months. There were no immediate complications. Stone clearance was confirmed by ultrasound and abdominal x-ray at 3–6 months after the procedure. Median follow-up was 15 (range 3–53) months. There were no leaks or difficulties catheterising the channel on follow-up. Discussion: This was the first series of Mitrofanoff/Monti cystolitholapaxy for the treatment of calculi in augmented bladders of paediatric patients. Previous concerns about damaging the continence mechanism of the conduit appeared to be unwarranted. The use of an Amplatz sheath protected the continence system from repeated instrumentation, and permitted free backflow of irrigation and rapid clearance of stone fragments. Recurrence of stones occurred in 38%, which was in keeping with rates reported in the wider literature. Conclusion: Mitrofanoff cystolitholapaxy was safe, and with appropriate care did not result in leakage or difficulty catheterising. Summary Table Amplatz sheath Number No sheath 4 18 Ch 13 20 Ch 3 26 Ch 1 28 Ch 1 Fragmentation method Number Swiss Lithoclast 12 Grasper 6 Laser 1 No fragmentation (lift-out) 3 Retrieval method Number Grasping forceps 18 2.4 Ch basket 4 Operative details.